Chinese (Taiwan) Yearbook of International Law and Affairs. Volume 36 (2018) - Ma, Ying-jeou 1950- (Brill Nijhoff, 2020)
Intro -- Contents -- Preface -- Ying-jeou Ma -- Articles -- Economics and International Law: Closer Alignment through Greater Analytical Diversity? -- Roda Mushkat -- Transnational Corporate Governance Codes: Lessons from Regulating Related Party Transactions in Hong Kong and Singapore -- Christopher Chen &amp -- Wai Yee Wan -- Essays and Special Reports -- Creative Contacts: Taiwan's Quest for International Law Enforcement Cooperation -- Margaret K. Lewis -- The Taiwan Travel Act is Legally Binding -- Julian G. Ku -- Taiwan's Antitrust Leniency Policy and the Framework to Build an Effective Antitrust Compliance Program -- Siao-Wun Chiu -- Belt and Road Dispute Resolution: New Development Trends -- Weixia Gu -- Demystifying China's International Commercial Court Regime: International or Intra-National? -- Huiqin Jiang -- Book Review -- Reconceptualizing International Investment Law from the Global South Edited by Fabio Morosini &amp -- Michelle Ratton Sanchez Badin, Cambridge University Press (2018), pp 305 -- Han-Wei Liu -- Contemporary Practice and Judicial Decisions of the Republic of China (Taiwan) Relating to International Law, 2018 -- Compiled by Chun-i Chen, Pasha L. Hsieh, Pei-Lun Tsai, Chun-Liang Lai, I-Hon Hsiao, and Kai-Chih Chang, with the Assistance of Lee &amp -- Li Attorneys-at-Law -- Explanatory Note -- I International Law in General -- Foreign Policy Report, 9th Congress of the Legislative Yuan, 5th Session (May 17, 2018) -- President Tsai Attends Opening of 2018 Asia-Pacific Security Dialogue -- Foreign Policy Report, 9th Congress of the Legislative Yuan, 6th Session (October 22, 2018) -- II Subjects of International Law -- III International Organizations -- Republic of China (Taiwan) and Intergovernmental Organizations